Endogenous noradrenaline release from guinea-pig isolated trachea is inhibited by activation of M2 receptors. - Racké, K. (1992)
Overflow of endogenous noradrenaline (NA) from guinea-pig isolated tracheae was evoked by electrical field stimulation (3 Hz, 540 pulses). The muscarinic receptor agonist oxotremorine inhibited the evoked overflow of NA in a concentration-dependent manner (EC50 84 nM). Methoctramine, pirenzepine and p-fluoro-hexahydrosiladiphenidol (each 1 microM) shifted the concentration-response curves of oxotremorine to the right with apparent pA2 values of 7.60, 6.74 and 6.18, respectively. It is concluded that sympathetic nerve terminals in the guinea-pig trachea are endowed with inhibitory muscarinic M2 receptors.